Wealth-related inequalities in undernutrition among under-five children in sub-Saharan Africa - Rahel Mulatie Anteneh; Natnael Moges; Asaye Alamneh Gebeyehu; Denekew Tenaw Anley; Ermias Sisay Chanie; Sintayehu Simie Tsega; Ermiyas Alemayehu; Melaku Ashagrie Belete; Natnael Kebede; Zufan Alamrie Asmare; Matyas Adugna; Zekaryas Ewnetu Gashu; et al. (Scientific Reports)
Abstract Undernutrition among under five children is a significant public health concern and a key factor in child mortality in developing nations. Addressing early childhood health disparities requires increased focus, as these issues are likely to persist into adulthood. This study examined wealth based inequalities in under-five undernutrition across 35 sub-Saharan African countries. This study utilized a total of 202,290 weighted samples from Demographic and Health Survey datasets across 35 sub-Saharan African countries. Data cleaning was performed using MS Excel, followed by extraction and analysis with STATA V.17 software. To assess wealth-related inequalities in undernutrition, the concentration index and curve, along with Wagstaff decomposition analysis, were employed. A p value of less than 0.05 was considered statistically significant. The overall pooled prevalence of undernutrition among children under five in sub-Saharan Africa was found to be 35.5% (95% CI 32.08, 38.88%), with a high heterogeneity (I2 = 99.9%). Prevalence rates varied significantly, ranging from 17.25% in Gabon to 58.57% in Burundi. The concentration index for wealth-related inequality in undernutrition indicated a pro-poor distribution, with a value of CI − 0.1719 (95% CI − 0.179, − 0.165) and a standard error of 0.0037 (p value < 0.0001). The decomposition analysis revealed that factors such as media exposure, access to improved water sources, improved toilet facilities, and maternal education were inversely associated with undernutrition. In contrast, living in rural areas and maternal occupation showed a positive association with undernutrition. Wealth related disparities to undernutrition showed a trend that favored poorer populations. Individuals from lower socioeconomic backgrounds were more likely to experience undernutrition compared to those from higher socioeconomic groups. Key factors contributing to wealth-related inequalities in child undernutrition included media exposure, place of residence, and access to sanitation facilities. The persistence of these inequalities highlights a significant social injustice. To effectively reduce these disparities, it is essential to implement integrated interventions during early life that address the multiple challenges faced by disadvantaged children. Therefore, policies should take into account the distribution of childhood undernutrition across all socioeconomic groups.